The Urgency of Special Legislation for Indigenous Peoples in Indonesia: Strengthening Legal Protection and Cultural Heritage - Rayhan, Ahmad; Putri, Winda Talita; Nugroho, Farhan Ardhi (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
Indigenous communities in Indonesia are vital to preserving the nation’s rich cultural diversity and local wisdom. They safeguard a heritage that spans ancient languages, customs, and traditional knowledge. However, these communities face challenges such as the legal recognition of customary land, the protection of basic rights, and environmental preservation. This study employs a normative legal research method to analyse relevant laws and regulations regarding the existence and protection of indigenous communities. It highlights the urgency of enacting specific legislation to safeguard their rights and improve their social and environmental welfare. The findings show that while indigenous communities are numerous, diverse, and widely distributed, they often suffer from the erosion of their rights—including customary land rights (Ulayat Land), the right to revive traditions, and the right to live as Indigenous Peoples. Despite partial efforts by the government through the 1945 Constitution, the Agrarian Law, and the Human Rights Law, a clearer and more robust legal framework in the form of a Special Law on Customary Communities is needed. Such legislation would enhance legal protection and address legitimacy challenges, ultimately strengthening the safeguarding of indigenous rights across Indonesia.